The Role of Local Wisdom in Realizing The Principle of Environmental Sustainability Principles in Indonesia: Peran Kearifan Lokal Dalam Mewujudkan Prinsip Keberlanjutan Lingkungan Hidup di Indonesia - Nurhasan; Bunyamin (LITIGASI, 2025)
The Local Wisdom of coastal communities has high effectiveness in maintaining the sustainability of marine and coastal ecosystems. However, challenges such as lack of legal recognition, changes in people’s lifestyles, and economic pressures are factors that hinder the sustainability of traditional fishing practices. Therefore, a strategy is needed that harmonizes government regulations with local wisdom practices in order to create a more sustainable and inclusive marine environmental management model. Local wisdom possessed by coastal communities in the archipelago is an important instrument for realizing the principles of environmental sustainability. The role of local wisdom in realizing the principle of environmental sustainability is important, especially for strengthening aspects of legal culture within the framework of an integrated legal system. Local wisdom of coastal communities describes a system that integrates knowledge, norm, culture and institutions as well as practices for managing marine fisheries resources, in line with the principles of harmony, balance and sustaibility. Cultural approaches through the application of local wisdom forms of coastal communities in the archipelago are important in order to support the effectiveness of supervision and law enforcement efforts in marine areas through a preventive approach, and have the potential to be added as one of the elements of the principles of environmental sustainability. This study uses a normative legal approach and a qualitative legal data analysis method using relevan legal interpretation methods. The formulation of a conceptual model regarding the role of local wisdom in realizing the principles of environmental sustainability is the aim of this research.